2006
DOI: 10.1111/j.1365-294x.2006.02818.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling and local adaptation of Boechera holboellii populations for water use efficiency across a naturally occurring water stress gradient

Abstract: We studied the physiological basis of local adaptation to drought in Boechera holboellii, a perennial relative of Arabidopsis thaliana, and used cDNA-AFLPs to identify candidate genes showing differential expression in these populations. We compared two populations of B. holboellii from contrasting water environments in a reciprocal transplant experiment, as well as in a laboratory dry-down experiment. We continuously measured the water con tent of soils using time domain reflectometery (TDR). We compared popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 69 publications
5
85
2
Order By: Relevance
“…Although it is unknown whether our study populations are at ecological or genetic equilibrium, they have not been impacted by habitat destruction and introduced genotypes, which complicates evolutionary inferences in weedy ephemerals such as A. thaliana and Capsella rubella. We have shown that Boechera populations are locally adapted to some of the ecological differences among these diverse habitats (Knight et al 2006). To understand the evolutionary processes that influence ecologically important trait variation in natural populations requires positional cloning, genetically undisturbed populations, and the opportunity to compare the fitness of QTL alleles in their natural environments.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is unknown whether our study populations are at ecological or genetic equilibrium, they have not been impacted by habitat destruction and introduced genotypes, which complicates evolutionary inferences in weedy ephemerals such as A. thaliana and Capsella rubella. We have shown that Boechera populations are locally adapted to some of the ecological differences among these diverse habitats (Knight et al 2006). To understand the evolutionary processes that influence ecologically important trait variation in natural populations requires positional cloning, genetically undisturbed populations, and the opportunity to compare the fitness of QTL alleles in their natural environments.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested that structural plant defenses or phenological avoidance of herbivores have a greater pleiotropic effect than more herbivore-specific chemical defenses (Carmona et al 2011). For example, specific leaf area (SLA) (a physical leaf trait) relates directly to water use in plants ( Knight et al 2006), but the silencing of drought-stress pathways in tomato plants had little effect on a suite of chemical markers of plant defense (Thaler and Bostock 2004).…”
Section: Global Patterns Of Leaf Defenses In Oak Speciesmentioning
confidence: 99%
“…Some authors have suggested that structural plant defenses or phenological avoidance of herbivores have a greater pleiotropic effect than more herbivore-specific chemical defenses (Carmona et al 2011). For example, specific leaf area (SLA) (a physical leaf trait) relates directly to water use in plants ( Knight et al 2006), but the silencing of drought-stress pathways in tomato plants had little effect on a suite of chemical markers of plant defense (Thaler and Bostock 2004).In this study, we examine the evolutionary history of oaks (Quercus) and use that phylogeny to investigate how the evolution of a suite of nine defensive traits correlates with various dimensions of the climatic environment and latitude. An index of these same traits has independently been shown to reduce the fitness of a generalist herbivore on oaks (Pearse 2011), and many other studies support the importance of these traits as leaf defenses against other herbivores (detailed in section Methods).…”
mentioning
confidence: 99%
“…In fact, both shifts in distribution and persistence in-situ by plants may include microevolution as a fundamental response to changing climate (Davis et al 2005;Norberg et al 2012). Plant population genetic structure has changed in the past, and is currently changing, in response to variation in climate (Davis et al 2005;Knight et al 2006;Parmesan 2006;Travers et al 2010;Alsos et al 2012).…”
Section: Introductionmentioning
confidence: 99%